2011
DOI: 10.4013/gaea.2011.71.02
|View full text |Cite
|
Sign up to set email alerts
|

Lenhos permianos da Bacia do Paraná, Brasil: síntese e revisão taxonômica

Abstract: A taxonomia dos lenhos permianos da bacia do Paraná remonta ao final do século XIX e inaugura com a descrição de Dadoxylon pedroi, identificado por Zeiller (1895) nas camadas de carvão da Formação Rio Bonito expostas no Vale do Jaguarão, no estado do Rio Grande do Sul. Entretanto, somente a partir de meados do século XX este tipo de pesquisa ganhou impulso, com as revisões e identificações feitas por Kräusel e Dolianiti (1958) e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Merlotti and Kurzawe (2011) attributed the stratigraphic position of the solenoid taxon Ductosolenoxylon and the nonsolenoid taxa Paulistoxylon, Abietopitys, Septomedulloxylon, Corticoxylon and Vertebraria to the Serra Alta Formation, which overlies the Irati Formation in the southern part of the basin. However, new results obtained by Guerra-Sommer during field expedition revealed that these woods were included in the topmost horizon of the Irati Formation (unpublished data).…”
Section: Fossil Woods As Correlation Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Merlotti and Kurzawe (2011) attributed the stratigraphic position of the solenoid taxon Ductosolenoxylon and the nonsolenoid taxa Paulistoxylon, Abietopitys, Septomedulloxylon, Corticoxylon and Vertebraria to the Serra Alta Formation, which overlies the Irati Formation in the southern part of the basin. However, new results obtained by Guerra-Sommer during field expedition revealed that these woods were included in the topmost horizon of the Irati Formation (unpublished data).…”
Section: Fossil Woods As Correlation Toolsmentioning
confidence: 99%
“…Woods from some localities for this time interval have been described by many authors in both regions (as synthesized by Merlotti andKurzawe, 2011 andPrasad, 1982), featuring in some cases preserved central pith.…”
Section: Introductionmentioning
confidence: 99%
“…The genera of Solenopitys and Atlanticoxylon are restricted to the Permian, with Solenopitys being more widely distributed in the southern part of Gondwanaland, from the Paraná Basin in the south of Brazil (Irati Formation; Mussa 1986) to the Falkland Islands (Mussa 1986), South Africa and Antarctica (Merlotti and Kurzawe 2011). Atlanticoxylon, on the other hand, was limited to the Paraná Basin (Irati Formation, Mussa 1986; Merlotti and Kurzawe 2011) and India (Guerra-Sommer et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…30.8). Some attempts to validate those taxa were made by Merlotti (2009) and Merlotti and Kurzawe (2011), whereas a few problems still remain unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…The Jaccard Coefficient is also a very powerful tool for analysing data regarding presence-absence with no importance on abundance (Legendre and Legendre, 1998;Hammer et al, 2001). Thus, cluster and Jaccard Coefficient analyses were undertaken to compare some Moscovian to Cisuralian anatomically preserved floras presented by Hilton and Cleal (2007), augmented by European floras from the Perdasdefogu Basin, Sardinia/Italy (Galtier et al, 2011), Grand-Croix, Saint-Étienne Basin, and Autun/France (Galtier, 2008), Leukersdorf Formation of the Petrified Forest of Chemnitz/Germany , Semily and Vrchlabí formations from Krkonoše Piedmont Basin/Nova Paka/Czech Republic (data provided by Dr. Vaclav Mencl, 2015), and Irati Formation from the Paraná Basin, southern Brazil (Mussa, 1978a(Mussa, ,b, 1982(Mussa, , 1986Mussa et al, 1980;Merlotti, 2009;Merlotti and Kurzawe, 2011). Hilton and Cleal (2007) presented an analysis of 19 Euramerican and Cathaysian floras, ranging from early Bashkirian up to Asselian-Sakmarian age.…”
Section: Fascicular Wedges Well Defined Throughout the Woodmentioning
confidence: 99%